2005
DOI: 10.1158/0008-5472.can-04-2667
|View full text |Cite
|
Sign up to set email alerts
|

EphB4 Expression and Biological Significance in Prostate Cancer

Abstract: Prostate cancer is the most common cancer in men. Advanced prostate cancer spreading beyond the gland is incurable. Identifying factors that regulate the spread of tumor into the regional nodes and distant sites would guide the development of novel diagnostic, prognostic, and therapeutic targets. The aim of our study was to examine the expression and biological role of EphB4 in prostate cancer. EphB4 mRNA is expressed in 64 of 72 (89%) prostate tumor tissues assessed. EphB4 protein expression is found in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
139
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 51 publications
(58 reference statements)
11
139
0
Order By: Relevance
“…However, there is growing evidence that EphB4 may provide more direct survival cues to cancer cells. We have shown recently such a role of EphB4 in prostate (Xia et al, 2005), bladder , breast , and head and neck cancers (Masood et al, 2006). In this report, we extend those findings to ovarian cancer as well.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…However, there is growing evidence that EphB4 may provide more direct survival cues to cancer cells. We have shown recently such a role of EphB4 in prostate (Xia et al, 2005), bladder , breast , and head and neck cancers (Masood et al, 2006). In this report, we extend those findings to ovarian cancer as well.…”
supporting
confidence: 82%
“…Similarly, treatment of HOC-7 cells with 25 nM EphB4 siRNA resulted in 75% reduction in cell numbers (data not shown). Treatment of EphB4-negative tumour cell lines with EphB4 siRNA does not affect tumour cell numbers (Xia et al, 2005 and data not shown).…”
Section: Inhibition Of Ephb4 Results In Reduced Viabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…Overexpression of EphB4 has been documented in other epithelial cancer types, including breast cancer (Berclaz et al, 1996), uterine caner (Berclaz et al, 2003), prostate cancer (Xia et al, 2005b) and mesothelioma (Xia et al, 2005a). Ours is the first report of EphB4 overexpression in bladder cancer.…”
Section: Discussionmentioning
confidence: 65%
“…Although Fc fusion proteins are quite stable when administered systemically in vivo, Eph receptor-and ephrin-based agents lack selectivity because of the promiscuity of Eph receptor-ephrin binding (section 1.3). More selective Eph receptor-targeting reagents that have been developed include antagonistic peptides that target the ephrin-binding site of individual Eph receptors (91,92), siRNAs and anti-sense oligodeoxynucleotides (93)(94)(95).…”
Section: Targeting Eph Receptor-ephrin Interactions To Modulate Angiomentioning
confidence: 99%